2017
DOI: 10.1177/0956797616687015
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Suggestion: Posthypnotically Induced Changes in the Temporal Binding of Intentional Action Outcomes

Abstract: The sense of agency is the experience of initiating and controlling one’s voluntary actions and their outcomes. Intentional binding (i.e., when voluntary actions and their outcomes are perceived to occur closer together in time than involuntary actions and their outcomes) is increased in intentional action but requires no explicit reflection on agency. The reported experience of involuntariness is central to hypnotic responding, during which strategic action is experienced as involuntary. We report reduced int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 31 publications
0
37
0
1
Order By: Relevance
“…As with explicit judgments of agency, Yoshie and Haggard (2013) found that temporal binding was moderated by whether the outcomes resulting from actions were positive or negative (though see Barlas et al, 2018; Moreton, Callan, & Hughes, 2017). Manipulations that influence whether participants believe they are responsible for an action, such as varying whether actions are freely chosen versus carried out under instruction, coercion, or hypnosis, also have an impact on temporal binding (Borhani et al, 2017; Caspar et al, 2016; Lush et al, 2017). Furthermore, when participants do actually cause an outcome but believe it is a result of another person's actions, temporal binding is reduced or abolished (Desantis et al, 2011).…”
Section: Temporal Binding As a Measure Of A “Pre‐reflective Sense Of mentioning
confidence: 99%
See 2 more Smart Citations
“…As with explicit judgments of agency, Yoshie and Haggard (2013) found that temporal binding was moderated by whether the outcomes resulting from actions were positive or negative (though see Barlas et al, 2018; Moreton, Callan, & Hughes, 2017). Manipulations that influence whether participants believe they are responsible for an action, such as varying whether actions are freely chosen versus carried out under instruction, coercion, or hypnosis, also have an impact on temporal binding (Borhani et al, 2017; Caspar et al, 2016; Lush et al, 2017). Furthermore, when participants do actually cause an outcome but believe it is a result of another person's actions, temporal binding is reduced or abolished (Desantis et al, 2011).…”
Section: Temporal Binding As a Measure Of A “Pre‐reflective Sense Of mentioning
confidence: 99%
“…For instance, Yoshie and Haggard (2017) conclude from the fact that the influence of outcome valence on temporal binding depends on the predictability of the outcome valence that “a special link between the brain systems for computing valence and reward, and the brain systems for predictive control of action” (p. 1) is responsible for the effect. Similarly, Lush et al (2017) conclude from the fact that hypnosis affects temporal binding that hypnosis changes the experience that people have when they act as well as influencing their reports about how voluntary their actions feel. The authors explicitly contrast this with the alternative hypothesis that the experience of actions carried out under hypnosis is actually the same as the experience of ordinary voluntary actions, and they argue that the fact that hypnosis affects both explicit verbal reports of agency and temporal binding is evidence against this alternative hypothesis.…”
Section: Temporal Binding As a Measure Of A “Pre‐reflective Sense Of mentioning
confidence: 99%
See 1 more Smart Citation
“…While IB is sensitive to experiences of agency, temporal binding also occurs between events believed to be causally related, and the magnitude of IB can be the same for both intentional and causal binding when conditions are well matched . It has recently been claimed that IB is unrelated to action intention, because binding is driven by the relative precision of action and outcome cues .…”
Section: Discussionmentioning
confidence: 99%
“…Hypnosis and hypnotic suggestions have been shown to be useful experimental tools to test theories of cognitive neuroscience (Oakley & Halligan, 2013;Raz, 2011), especially theories related to consciousness (Cardeña, 2014;Terhune, Cleeremans, Raz, & Lynn, 2017). For instance, hypnotic suggestions can evoke changes in the feeling of voluntariness (Weitzenhoffer, 1974(Weitzenhoffer, , 1980 or even modify one`s sense of agency (Haggard, Cartledge, Dafydd, & Oakley, 2004;Lush et al, 2017;Polito, Barnier, & Woody, 2013). Responses to suggestions frequently involve alterations in perception, such as the experience of positive and negative hallucinations or delusions (Kihlstrom, 1985;Oakley & Halligan, 2009).…”
mentioning
confidence: 99%